2021
DOI: 10.3389/fimmu.2021.635072
|View full text |Cite
|
Sign up to set email alerts
|

Immune Response to Enterococcus gallinarum in Lupus Patients Is Associated With a Subset of Lupus-Associated Autoantibodies

Abstract: Interactions between gut microbes and the immune system influence autoimmune disorders like systemic lupus erythematosus (SLE). Recently, Enterococcus gallinarum, a gram-positive commensal gut bacterium, was implicated as a candidate pathobiont in SLE. The present study was undertaken to evaluate the influence of E. gallinarum exposure on clinical parameters of SLE. Since circulating IgG antibodies to whole bacteria have been established as a surrogate marker for bacterial exposure, anti-E. gallinarum IgG anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 40 publications
(43 reference statements)
0
16
0
Order By: Relevance
“…Murine models have also provided evidence that gut barrier defects and translocation of commensals, their antigens, and in some cases live bacteria have been recoverable from draining lymph nodes and the liver ( 37 ). However, a subsequent report found sera from both patients with SLE as well as healthy controls had IgG and IgA antibodies reactive with E. gallinarum ( 38 ), suggesting this commensal is not a common driver of uncomplicated SLE. Taken together, dysfunctional intestinal barrier integrity has been documented in three lupus mouse models ( 37 , 39 , 40 ), while severe lupus-like disease arises in the B6.Sle1.Sle2.Sle3 mouse without evidence of altered gut barrier permeability or commensal translocation ( 34 ).…”
Section: Discussionmentioning
confidence: 97%
“…Murine models have also provided evidence that gut barrier defects and translocation of commensals, their antigens, and in some cases live bacteria have been recoverable from draining lymph nodes and the liver ( 37 ). However, a subsequent report found sera from both patients with SLE as well as healthy controls had IgG and IgA antibodies reactive with E. gallinarum ( 38 ), suggesting this commensal is not a common driver of uncomplicated SLE. Taken together, dysfunctional intestinal barrier integrity has been documented in three lupus mouse models ( 37 , 39 , 40 ), while severe lupus-like disease arises in the B6.Sle1.Sle2.Sle3 mouse without evidence of altered gut barrier permeability or commensal translocation ( 34 ).…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, pathogen-specific therapy can suppress host autoimmune processes without the use of immunosuppressants. More recently, another study showed that E. gallinarum is associated with autoimmune responses to autoantibodies such as anti-Ribosomal P, anti-dsDNA, and anti-Sm in patients with SLE ( 61 ). This study further confirmed that E. gallinarum is a specific pathogen of SLE-susceptible individuals.…”
Section: Mechanisms Of Gut Microbiota Dysbiosis In Slementioning
confidence: 99%
“…There is evidence that intestinal expansion of this species leads to cross-reaction with lupus anti-double stranded DNA (dsDNA) antibodies and correlated with lupus nephritis. 38 Bagavant et al 54 also found an increase in Enterococcus gallinarum in patients with SLE and that this was significantly associated with the presence of anti-dsDNA and anti-Sm autoantibodies. However, we cannot infer changes at the level of the species or genus based on changes at the level of the family, as determined by 16S RNA data.…”
Section: Discussionmentioning
confidence: 91%